Therapeutic Efficacy of Tinospora cordifolia and CeftiofurSodium in Crossbred Cows Affected with Endometritis - Dodiya, Ranjeetsinh V; Nakhashi, Haresh C; Chaudhary, Panchabhai H; Vaghasiya, Yash H; Suthar, Babulal N (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Clinical research to evaluate the therapeutic efficacy of Tinospora cordifolia and ceftiofur sodium in crossbred cows affected with endometritis was undertaken. Group I consisted the treatment with ceftiofur sodium 1gm intrauterine once, and Group II with 1 g Tinospora cordifolia dissolved in 50 ml normal saline, intrauterine for 3 days in crossbred cows numbering 10 in each group. White side and leukocyte esterase tests were performed before and after treatment. All the cows were inseminated with frozen semen at subsequent estrus. Based on the reactivity to white side test following the treatment, 80 per cent (8/10) in Group I and 70 per cent (7/10) cows were found recovered and the overall conception rate was higher (60%) in Group I followed by 40 per cent in Group II.
Keywords: Ceftiofur sodium; Endometriti; Leukocyte esterase test